Kontribusi Unsur-Unsur Dinamis Pembelajaran, Fasilitas Belajar, dan Motivasi Berprestasi Terhadap Kepuasan Siswa Kelas VIII MTS Ta'mirul Islam Surakarta - Hatta, Muhammad, Prof. Dr. Sutama, M.Pd, Dr. Sabar Narimo, M.M, M.Pd (2016)
The purpose of this study there are four, the first test and analyze the contribution of dynamic elements of learning, learning, and achievement motivation on student satisfaction, second, test and analyze the contribution of dynamic elements of learning to student satisfaction, third, test and analyze the contribution of learning facility to the satisfaction of the students, the fourth test and analyze the contribution of achievement motivation on student satisfaction. Quantitative research, research design ex-post facto by the correlation technique. Research conducted at MTs Ta 'mirul Islam Surakarta in the second semester of the school year 2015/2016 with a sample of 105 students. The sampling technique using proportional random sampling using krecii table. Data collection techniques in this study using questionnaires and observation. Data analysis techniques used in this research is multiple regression analysis after classical assumption test such as the test for normality, linearity test, test multicollinearity, heteroscedasticity test and autocorrelation test.The results of the study there were four, (1) there are contribution dynamic elements of learning, learning, and achievement motivation in a significant 0.05 on student satisfaction was 27.5%, (2) there isa contributions dynamic elements of learning at 0.048 significant on student satisfaction and contribute effectively amounted to 6.49%, (3) there is a significant contribution of the teaching facilities at 0,012 to student satisfaction and contribute effectively amounted to 9.69%, (4) there is a significant contribution to the achievement motivation 0.05 on student satisfaction and contribute effectively 11.32%. Keywords: learning facilities, achievement motivation, learning dynamic element, satisfaction